(untitled) (The Research of Medical Science Review, 2025)
The present study was conducted to explore the relationship between social media use and related affect (positive affect and negative affect) and internalization of socio-cultural attitudes towards appearance (thin body fat, muscular, pressure from family, pressure from peers, and pressure from media) in eating problems among adults. Differences across gender and other of demographic variables in the proposed relationships were also studied. Research variables were measured by using Eating Disorder Examination-Questionnaire (Fairburn & Beglin, 1994), Socio-cultural Attitudes Towards Appearance Questionnaire-4 (Schaefer et al., 2013), Social Networking Sites (SNSs) Usage Questionnaire (Shi et al., 2013), and a demographic sheet were used for data collection through online survey taken up due to COVID-19 Lock Down. Sample was drawn conveniently comprising of Pakistani adults (N = 266) with minimum age 18 years and having English language skills to respond. Analysis was conducted through SPSS-22. Alpha coefficients of the measures were found to be satisfactory. Findings showed that social media use was significantly positively related to eating problems. Internalization of pressure regarding socio-cultural attitudes towards appearance by family, media, peers, having thin, and muscular body had a significant positive relationship with eating problems. There was non significant differences between male and female participants on eating problems and its domain; eating concern, shape concern, weight concern, and restraint. It was found that thin body fat, pressure from family, and pressure from media were significantly predicting eating problems. There were significant differences between male and female participants on socio-cultural attitude towards appearance and its domains; muscular, pressure from family, and pressure from media. Men had more internalization of muscular body ideal of socio-cultural attitudes towards appearance than women. Findings were discussed in the light of past literature and cultural context. The results and implications were discussed in Pakistani context.